PENGEMBANGAN BUKU PANDUAN PENILAIAN MULTIMEDIA PEMBELAJARAN - Sungkono Sungkono; Novi Trilisiana; Mulyo Prabowo (Akademika : Jurnal Teknologi Pendidikan, 2022)
This study aims to 1) produce a proper multimedia learning assessment guidebook, 2) determine the feasibility level of a multimedia learning assessment guidebook. This research is a type of three-stage research and development of the four stages of Thiagarajan namely Define, Design, and Development. The research subjects are the review media, review instruments, and students. The results of this research are made into a book that has an ISBN so that it can be widely used by the public. The resulting multimedia assessment guidebook product is in the form of a printed book that has a variety of colors; physical appearance; design text, images, and charts according to the characteristics of students and validators. The results of the media expert's assessment of the guidebook are offered as very feasible. The results of the expert assessment (material) of the guidebook are categorized as very feasible. So, the overall assessment of the book means that it is very worthy of publication. Multimedia assessment guidebooks are recommended for use in tertiary institutions that focus on research and development of multimedia learning products. The guidebook can be disseminated to the campus academic community as users to find out the effectiveness and usefulness of the guidebook for further research